Pengaruh Promosi Kualitas Pelayanan dan Lokasi Terhadap Kepuasan Pelanggan di Hotel Des Indes Menteng - Arya Dwi Wanandi; Hairani Tarigan (LPPM Universitas Asa Indonesia, 2022)
The study intends to investigate the influence of advertising, service quality, location on customer satisfaction. This research is a quantitative research by distributing quiestionnaires. The population in this study are clients who stay at the Hotel Des Indes Menteng. The sample approach employed accidental sampling as many as 100 respondents. The data collecting approach employs a questionnaire presented to respondents and this analysis uses multiple linear regression, and is performed using the Smart PLS 3 program. The data demonstrate that the influence of advertising, service quality, and location has a favorable and significant effect on customer satisfaction. This ideas in this study are verified correct.